Prospective study of laparoscopic management of appendicitis during the COVID pandemic in a single paediatric centre - Dipankar Dass; Sesi Hotonu; Merrill McHoney; Fraser Munro (Wolters Kluwer Medknow Publications, 2023)
Background: The coronavirus (COVID-19) pandemic affected the presentation of many conditions. This study analyses and describes the impact of the COVID-19 pandemic on the management of appendicitis in children and the role of laparoscopy. Materials and Methods: We performed a prospective (during the pandemic) and retrospective (historic control) review of the management of appendicitis in a tertiary paediatric surgical unit. Preoperative data, operative findings and patient outcomes were compared between groups to identify differences between the study periods and to identify any factors predictive of outcomes. Results: Sixty-two patients were identified in the pre-pandemic cohort, 72 in the pandemic cohort. There was no significant difference in patient demographics, length of admission or time between admission and surgery between groups. There was however a significantly longer time to presentation to hospital in the pandemic group. Clinical outcomes were comparable between the two groups, with no difference in the presence of surgical complications or histologically advanced appendicitis between the two groups. Laparoscopic surgery was safely used to manage appendicitis in the pandemic cohort through utilisation of a COVID-19 pathway that included guidance on testing, and use of personal protective equipment (PPE). Conservative management in the pandemic cohort was reserved for patients with appendicitis with the presence of mass formation. Conclusion: Despite a delayed presentation to hospital, there was no rise in the incidence of complicated appendicitis, complications of surgery or length of stay during the COVID-19 pandemic. Laparoscopic appendicectomy was also shown to be a safe and effective standard for the management of appendicitis during the pandemic. Level of Evidence: III, treatment.